EVALUASI EFEKTIVITAS DAN EFISIENSI ANGKUTAN UMUM DI KAWASAN TEMBALANG - Marla Ayu Kusumawardani; Robbiatul Adawiyah; Bambang Riyanto; Amelia Kusuma Insriastuti (Jurnal Karya Teknik Sipil, 2013)
The imbalance between need and supply on public transportation at Tembalang territory has caused the drivers do not obey their fixed route, so it reduces user’s comfort. Therefore, it needs an evaluation for effectiveness and efficiency on public transportation so that public transportation performance can be improved. Primary data gained from questioner, static survey or dynamic and analyzed to be quantitative indicator. Qualitative indicator is using Important Performance Analysis (IPA) method.  The analysis result will be compared to Standar Pedoman Teknis Penyelenggaraan Angkutan Umum di Wilayah Perkotaan Dalam Trayek Tetap dan Teratur (2002) and Sistranas year 2012 to reach a conclusion on public transportation performance at Tembalang territory. The research result shows that the movement pattern in Tembalang territory is uneven. While the result from qualitative indicator analysis shows well-matched result with existed regulation or stardart, in other words, public transportation in Tembalang territory is effective and efficient. However, this conclusion has not described comfort perception from public transportation’s user. Processing result using IPA method shows several indicators spread evenly to 4 quadrants, the important indicator and its quality needs to be improved are public transportation's comfort and waiting time. Enhancement on effectiveness and efficiency need to be done by improving all aspects starts from service, transportation renovation, until communication development between the community of public transportation and related parties when there is a decision related to public transportation can gained effective solution for both sides.